The military dimension of Turkey-Qatar relations and its security impacts / Badereddin Adnan Bader Seyam - Badereddin Adnan , Bader Seyam (2019)
The Turkish-Qatari relationship has witnessed progress in many areas gradually and progressively leading to strategic and military cooperation. This cooperation reached advanced stages after the launching of the Supreme Strategic Committee between the two countries in 2014 and the establishment of the Turkish military base in Qatar. This study examines the motives and factors that led the relationship between the two countries to strategic and military levels. The impact of this cooperation is examined in the regional security and on the relationship between Turkey and Qatar and other Arabian Gulf countries. The study also investigates the challenges to the sustainability of such cooperation. It applies a qualitative research approach to find answers to the above queries through triangulation data and by reviewing secondary literature including books, book chapters, journal articles, reports, press articles and government statements. Semi-structured interviews are also used directly through e-mail and other web applications with politicians and heads of political research centres, researchers, specialists and scientists who have knowledge of the region. The findings show that the similarity in the political positions towards the various regional issues and the increasing economic exchange are considered the motives that led the relationship to strategic-military cooperation. In addition, the state of mystery and strategic vacuum experienced by the region plays a significant role in this cooperation. Moreover, the outbreak of the Arabian Gulf crisis between Qatar on one hand and Saudi Arabia and the UAE on the other strengthened the Turkish-Qatari cooperation. The current study also found that the implementation of the military agreement between the two countries prevented disastrous consequences in the Arabian Gulf crisis and gave the opportunity to Turkey to market itself as a friend that the allied countries could trust. This cooperation has allowed Turkey to deploy its forces in the world's resource-rich and energy-rich region, overlooking vital trade corridors. In addition, Turkey has been denied the role as a mediator in some of the issues of the Arabian Gulf Cooperation Council (GCC). This rejection increases tensions in the relationship between Turkey and Qatar on the one hand, and Saudi Arabia and the UAE on the other. This study also found that this cooperation will face some challenges at the internal level, such as the stability of the governmental system of the two countries and transfer the relationship between them from senior leadership levels to the media and public opinion in both countries. Adding to that, the regional challenges of continuing the Arabian Gulf crisis lead to more violent options due to the Iranian influence in the region. At the international level, Western countries with military presence in the Arabian Gulf are pleased with the growing Turkish military presence. Their position will depend on their political positions in the region's issues, and all challenges will become realistic in accordance with volatile political and security changes in the area of conflict.